Nicotinic acid adenine dinucleotide phosphate activates two‐pore channel TPC1 to mediate lysosomal Ca2+ release in endothelial colony‐forming cells. Issue 1 (24th June 2020) - Moccia, Francesco; Zuccolo, Estella; Di Nezza, Francesca; Pellavio, Giorgia; Faris, Pawan S.; Negri, Sharon; De Luca, Antonio; Laforenza, Umberto; Ambrosone, Luigi; Rosti, Vittorio; Guerra, Germano
Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is the most recently discovered Ca 2+ ‐releasing messenger that increases the intracellular Ca 2+ concentration by mobilizing the lysosomal Ca 2+ store through two‐pore channels 1 (TPC1) and 2 (TPC2). NAADP‐induced lysosomal Ca 2+ release regulates multiple endothelial functions, including nitric oxide release and proliferation. A sizeable acidic Ca 2+ pool endowed with TPC1 is also present in human endothelial colony‐forming cells (ECFCs), which represent the only known truly endothelial precursors. Herein, we sought to explore the role of the lysosomal Ca 2+ store and TPC1 in circulating ECFCs by harnessing Ca 2+ imaging and molecular biology techniques. The lysosomotropic agent, Gly–Phe β‐naphthylamide, and nigericin, which dissipates the proton gradient which drives Ca 2+ sequestration by acidic organelles, caused endogenous Ca 2+ release in the presence of a replete inositol‐1, 4, 5‐trisphosphate (InsP3 )‐sensitive endoplasmic reticulum (ER) Ca 2+ pool. Likewise, the amount of ER releasable Ca 2+ was reduced by disrupting lysosomal Ca 2+ content. Liposomal delivery of NAADP induced a transient Ca 2+ signal that was abolished by disrupting the lysosomal Ca 2+ store and by pharmacological and genetic blockade of TPC1. Pharmacological manipulation revealed that NAADP‐induced Ca 2+ release also required ER‐embedded InsP3 receptors. Finally, NAADP‐induced lysosomal Ca 2+ release was found to trigger vascular endothelial growth factor‐induced intracellular Ca 2+ oscillations and proliferation, while it did not contribute to adenosine‐5′‐trisphosphate‐induced Ca 2+ signaling. These findings demonstrated that NAADP‐induced TPC1‐mediated Ca 2+ release can selectively be recruited to induce the Ca 2+ response to specific cues in circulating ECFCs. Abstract : Nicotinic acid adenine dinucleotide phosphate (NAADP) stimulated to the endolysosomal two‐pore channel 1 to mediate intracellular Ca 2+ signals in endothelial colony‐forming cells. NAADP‐induced endolysosomal (EL) Ca 2+ release was then amplified by inositol‐1, 4, 5‐trisphosphate receptors through the Ca 2+ ‐induced Ca 2+ ‐release process. NAADP‐induced EL Ca 2+ release triggered vascular endothelial growth factor‐induced proangiogenic Ca 2+ oscillations.